ChemInform Abstract: Photoredox Transformations with Dimeric Gold Complexes. Issue 22 (3rd June 2014) - Revol, Guillaume; McCallum, Terry; Morin, Mathieu; Gagosz, Fabien; Barriault, Louis
Abstract A light‐enabled reductive radical reaction of various unactivated alkyl and aryl bromides in the presence of a dimeric gold‐phosphine complex as catalyst is described.